Monday

May 25, 2015

May 25, 2015

Posted by **tara** on Thursday, October 28, 2010 at 8:35pm.

xy=1

4x-y+3=0

- algebra -
**Henry**, Friday, October 29, 2010 at 7:44pmxy = 1,

4x - y + 3 = 0.

Solve 1st Eq for x:

X = 1/y,

Substitute 1/y for x in EQ2:

4/y - y + 3 = 0,

Multiply both sides by -y:

-4 + y^2 - 3y = 0,

y^2 - 3y - 4 = 0,

Factor the trinomial:

(y + 1) (y - 4) = 0,

y + 1 = 0,

y = -1.

y - 4 = 0,

y = 4.

Substitute -1 for y in Eq1:

x*-1 = 1,

x = -1.

Substitute 4 for y in Eq1:

x * 4 = 1,

x = 1/4.

Solution set: (-1 , -1) , (1/4 , 4).